"Shots fired! We have many people down!": Common recommendations for managing high-casualty active shooter events in the USA. (November 2021) - Duron, Aaron
Abstract: Active shooter events are disasters that continue to impact communities and people in the United States. Responses to active shooter events by first responder organizations have improved since the Columbine event; however, problems still exist in these responses. Using systems theory and the qualitative method known as thematic analysis, the purpose of the current study was to examine the recommendations provided in after-action reports of high-casualty active shooter events to identify improvements that can be made by first responder organizations to provide a more effective response to active shooter events. Three main themes were identified and are discussed.